Enhancing Students’ Pronunciation Mastery Through Drama Technique in EFL Classroom at Islamic High School in Tasikmalaya - Suhada, Karina; Friatin, Lilies Youlia; Herlina, Rina (Universitas Galuh, 2025)
The fluency of pronunciation is influenced by how often the students say the words, so the more they speak, the better the pronunciation will be. To improve students' pronunciation abilities in learning English, appropriate techniques are needed. This research was conducted to find out drama techniques implemented to enhance students' pronunciation mastery of the EFL class in one Islamic Senior High School Tasikmalaya, and to learn about the challenges and opportunities during drama techniques implemented to improve their pronunciation mastery. This research used qualitative paradigm with the type of descriptive approach. The research subjects were typically students of 10th-grade in EFL classes who implemented drama techniques. There are five students and two teachers who were interviewed. The implementation of drama techniques in learning English in EFl classes to improve students' pronunciation is played in the classroom during learning hours and also outside of learning. In applying this drama technique, there are several steps taken by students and teachers in learning, namely determining the topic of the drama, compiling a drama script, dividing roles, practicing dialogue and performing the drama. There are five supporting factors in applying drama techniques to improve students' pronunciation, namely cooperation, environment, special schedule, and having competent supervisors and complete and adequate facilities provided. Meanwhile, the factors that hinder the implementation of drama techniques to improvestudents’ pronunciation in EFL classes are unequal understanding, lack of students’ interest and students’ participation in the program. Sometimes, students show the feeling of enthusiastic about learning and even feeling bored with these activities.